The Truman Show [videorecording (Blu-Ray)] - Rudin, Scott, 1958-; Niccol, Andrew; Feldman, Edward S., 1929-2020; Schroeder, Adam; Weir, Peter, 1944-; Carrey, Jim, 1962-; Linney, Laura; Emmerich, Noah; McElhone, Natascha, 1969-; Taylor, Holland; Harris, Ed, 1950- (Paramount Home Entertainment, 2008)
All eyes are on Truman Burbank. Truman is about to discover how abnormal his seemingly 'normal' life really is. Truman is an insurance salesman who begins to doubt reality. What he doesn't realize is that his whole life is a reality TV show, televised and broadcast for the world to see.